Penerapan Konseling Realita dan Mindfulness Untuk Mengatasi Kenakalan Remaja pada Siswa Broken Home - Sardi Sardi; Budianto Budianto; Joni Pranata; Suryanti Suryanti (Jurnal HUMMANSI (Humaniora, Manajemen, Akuntansi), 2021)
This paper was made with the aim of knowing how important the application of reality counseling is to address juvenile delinquency in broken home students and how important it is to apply mindfulness to overcome juvenile delinquency in broken home students. Juvenile delinquency is behavior that deviates from the prevailing norms in society and religion. Furthermore, a broken home is a crack in a family. The application of voluntary counseling and mindfulness is important to be implemented in schools considering that the problem of broken homen often occurs in students. The results of this article indicate that the application of two approaches, namely the reality counseling approach and mindfulness, has a positive and effective impact in overcoming juvenile delinquency caused by broken homes. The benefits that can be felt by the counselee or students after going through reality and mindfulness counseling are self-acceptance, responsibility, mentally becoming stronger and the formation of students who are patient, non-judgmental and mindful.